EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN TIPE THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK PADA MATERI BILANGAN DITINJAU DARI KEMANDIRIAN BELAJAR SISWA SMP DI KOTA SURAKARTA TAHUN AJARAN 2014/2015 - Astutik, Dian Dwi; Budiyono, Budiyono; Usodo, Budi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objectives of research were to find out: (1) which one gives better in mathematics achievement, cooperative learning model of Numbered Heads Together (NHT) or Think Pair Share (TPS) type or clasical learning model. (2) which one gives better in mathematics achievement, students who have high, medium, or low self-directed learning. (3) which one gives better in mathematics achievement, cooperative learning model of Numbered Heads Together (NHT), Think Pair Share (TPS) type or clasical learning model, in each of self-directed learning. (4) which one better Â mathematics achievement among students who have high, medium, or low self-directed learning, on each learning models. This research was quasi experimental research with 3 x 3 factorial design. The population of research was all of the VII graders of Junior High Schools in Surakarta City. The sample was taken using stratified cluster random sampling. The sample of research consisted of 273 students: 96 students for the experiment I, 93 students for experiment II and 84 students for experiment III. The instruments used for collecting data were mathematics learning achievement test and student learning style questionnaire. Testing of hypothesis used unbalanced two-ways analysis of variance using significance level ofÂ  Î± = 0,05. Based on hypothesis test, the conclusions were as follows. (1) Students who taught by cooperative learning model of NHT type have better mathematics achievement than students who teach by cooperative learning model of TPS type and classical learning model. On the other side, students who teach by cooperative learning model of TPS type produced the same mathematics achievement as using classical learning model. (2) Students with high self-directed learning had mathematics achievement better than students with medium or low self-directed learning, while students with medium self-directed learning produced the same mathematics achievement as with low self-directed learning. (3) In aech category high, medium and low self-directed learning, students who taught by cooperative learning model of NHT type have better mathematics achievement than students who teach by cooperative learning model of TPS type and classical learning model. On the other side, students who taught by cooperative learning model of TPS type have better mathematics achievement than classical learning model. (4) On each model of learning, cooperative learning model of NHT type, TPS type and classical learning model, students with high self-directed learning had mathematics achievement better than students with medium or low self-directed learning, while students with medium self-directed learning had mathematics achievement better than students with low self-directed learning.Keywords: Cooperative Learning of NHT, TPS, Self-Directed Learning, Mathematics Achievement.